Freezing of Biological Tissues During Cryosurgery Using Hyperbolic Heat Conduction Model - Singh, Sonalika; Kumar, Sushil (Mathematical Modelling and Analysis, 2015)
This paper considers hyperbolic heat conduction model for biological tissue freezing during cryosurgery with non ideal property of tissue, metabolism and blood perfusion. Mathematical model is solved numerically using finite difference method to obtain temperature distribution and phase change interfaces in tissue during freezing. The effects of phase lag of heat flux in hyperbolic bio-heat model on freezing process are studied. Comparative study of parabolic and hyperbolic bio-heat models is also made here.